Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Ferrite magnets do not deter blue sharks (Prionace glauca) from bait strikes in behavioural trials - Sol Lucas; Gonzalo Araujo; Rosalind M.K. Bown; Mark Johns; Samuel Matthews; Emma Nicol; Kristian J. Parton; Richard Rees; Gemma Scotts; Victoria Walker; Emma Williams; Per Berggren (Fisheries Research, 2025)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Leaching and volatilization of nitrogen in paddy rice under different nitrogen management - Majharul Islam; Md. Mizanur Rahman; Mohammad Saiful Alam; Robert Martin Rees; G. K. M. Mustafizur Rahman; Md. Giashuddin Miah; Julia Drewer; Arti Bhatia; Mark A. Sutton (Nutrient Cycling in Agroecosystems, 2024)

Reducing the environmental impact of rice production in subtropical India by minimising reactive nitrogen loss - Dibyendu Chatterjee; Saikat Ranjan Das; Sangita Mohanty; Baishnab Charan Muduli; Arti Bhatia; Bitish Kumar Nayak; Robert M. Rees; Julia Drewer; Amaresh Kumar Nayak; Tapan Kumar Adhya; Chidambaranathan Parameswaran; Jitendriya Meher; et al. (Journal of Environmental Management, 2024)

Fox control and fire influence the occurrence of invasive predators and threatened native prey - Matthew W. Rees; Brendan A. Wintle; Alan Robley; Jack H. Pascoe; Mark Le Pla; Emma K. Birnbaum; Bronwyn A. Hradsky (Biological Invasions, 2024)
It can be challenging to distinguish management impacts from other population drivers, including ‘natural’ processes and co-occurring threats. However, disentangling processes is important, particularly when management may have unintended consequences, such as mesopredator release. We explored the effects of long-term, broadscale poison-baiting programs on the distribution of red foxes Vulpes vulpes (targeted invasive predator), feral cats Felis catus (unmanaged invasive competitor) and two of their threatened native prey in two fire-affected regions of south-eastern Australia. We synthesised data from 3667 camera-trap deployments at 1232 sites (172,052 trap-nights), combining experimental manipulation of foxes and fire with space-for-time approaches. Fox control effectiveness—in terms of decreased probability of fox occurrence and increased probability of prey occurrence—depended on the duration and intensity of the poison-baiting program. The effects of fox control on prey occurrence also varied between the two native prey species: fox control was strongly beneficial to the long-nosed potoroo Potorous tridactylus but had no measurable effect on southern brown bandicoot Isoodon obesulus occurrence. Feral cat occupancy tended to be higher in landscapes with long-term fox control, although we found no effect of fox-bait density on fine-scale cat occurrence. Time since fire (0–80 years) was associated with the occurrence of each study species, but its association with invasive predators also differed among vegetation types. Invasive predators and altered fire regimes are key, often overlapping, biodiversity threats. Our work highlights the importance of fine-scale monitoring and consideration of multiple drivers in distribution models to develop effective, tailored conservation strategies.

Marine nutrient subsidies promote biogeochemical hotspots in undisturbed, highly humic estuaries - Chris D. Evans; Stacey L. Felgate; Steffi Carter; Mark Stinchcombe; Edward Mawji; Andrew P. Rees; Inma Lebron; Richard Sanders; Paul Brickle; Daniel J. Mayor (Limnology and Oceanography, 2023)
The land‐ocean dissolved organic carbon (DOC) flux represents a significant term within the global carbon budget, with peatland‐dominated regions representing the most intense sources of terrestrial DOC export. As the interface between freshwater and marine systems, estuaries have the potential to act as a filter of the land‐ocean carbon flux, removing terrestrially derived DOC, which is present at low concentrations in the oceans, via a combination of physicochemical and biological processes. However, the fate of peat‐derived DOC within estuaries remains poorly quantified, partly due to the complicating influences of heterogeneous soils, land‐use, point sources, and upstream modification of organic matter. To minimize these modifying factors, we studied DOC and inorganic nutrients in four small, peat‐dominated, minimally disturbed, and oligotrophic Falkland Island estuaries. Contrary to expectations, we found limited evidence of physicochemical estuarine DOC removal, and instead observed apparent “hot zones” of biogeochemical activity, where terrestrially‐derived silicate mixed with inorganic nitrogen and phosphorus entering the estuaries from the nutrient‐rich marine ecosystem. In two estuaries, this coincided with apparent in situ DOC production. We suggest that the observed phenomena of marine nutrient subsidy of estuarine productivity, and flexible utilization of multiple nutrients within the oligotrophic system, may once have been widespread in temperate estuaries. However, this function has been lost in many ecosystems due to catchment eutrophication by agricultural and urban development. We conclude that the estuaries of the Falkland Islands provide a valuable pre‐disturbance analogue for natural biogeochemical functioning in temperate estuaries receiving high organic matter inputs.

A critical comparison of integral projection and matrix projection models for demographic analysis: Comment - Stephen P. Ellner; Peter B. Adler; Dylan Z. Childs; Giles Hooker; Tom E. X. Miller; Mark Rees (Ecology, 2022)

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Joint associations of physical activity and body mass index with the risk of established excess body fatness-related cancers among postmenopausal women - Maret L. Maliniak; Susan M. Gapstur; Lauren E. McCullough; Erika Rees-Punia; Mia M. Gaudet; Caroline Y. Um; Mark A. Guinter; W. Dana Flanders; Alpa V. Patel (Cancer Causes & Control, 2021)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Re-analysis of archaeobotanical remains from pre- and early agricultural sites provides no evidence for a narrowing of the wild plant food spectrum during the origins of agriculture in southwest Asia - Michael Wallace; Glynis Jones; Michael Charles; Emily Forster; Eleanor Stillman; Vincent Bonhomme; Alexandra Livarda; Colin P. Osborne; Mark Rees; Georg Frenck; Catherine Preece (Vegetation History and Archaeobotany, 2019)

Rapid evolution with generation overlap: the double-edged effect of dormancy - Masato Yamamichi; Nelson G. Hairston; Mark Rees; Stephen P. Ellner (Theoretical Ecology, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Strong responses from weakly interacting species - Sean L. Tuck; Janielle Porter; Mark Rees; Lindsay A. Turnbull (Ecology Letters, 2018)
The impact of species loss from competitive communities partly depends on how populations of the surviving species respond. Predicting the response should be straightforward using models that describe population growth as a function of competitor densities; but these models require accurate estimates of interaction strengths. Here, we quantified how well we could predict responses to competitor removal in a community of annual plants, using a combination of observation and experiment. It was straightforward to fit models to multi‐species communities, which passed standard diagnostic tests and provided apparently sensible estimates of interaction strengths. However, the models consistently underpredicted the response to competitor removal, by a factor of at least 50%. We argue that this poor predictive ability is likely to be general in plant communities due to ‘the ghost of competition present’ that confines species to parts of the environment in which they compete best.

Global biogeography of mating system variation in seed plants - David A. Moeller; Ryan D. Briscoe Runquist; Annika M. Moe; Monica A. Geber; Carol Goodwillie; Pierre‐Olivier Cheptou; Christopher G. Eckert; Elizabeth Elle; Mark O. Johnston; Susan Kalisz; Richard H. Ree; Risa D. Sargent; et al. (Ecology Letters, 2017)
Latitudinal gradients in biotic interactions have been suggested as causes of global patterns of biodiversity and phenotypic variation. Plant biologists have long speculated that outcrossing mating systems are more common at low than high latitudes owing to a greater predictability of plant–pollinator interactions in the tropics; however, these ideas have not previously been tested. Here, we present the first global biogeographic analysis of plant mating systems based on 624 published studies from 492 taxa. We found a weak decline in outcrossing rate towards higher latitudes and among some biomes, but no biogeographic patterns in the frequency of self‐incompatibility. Incorporating life history and growth form into biogeographic analyses reduced or eliminated the importance of latitude and biome in predicting outcrossing or self‐incompatibility. Our results suggest that biogeographic patterns in mating system are more likely a reflection of the frequency of life forms across latitudes rather than the strength of plant–pollinator interactions.

The effects of asymmetric competition on the life history of Trinidadian guppies - Ronald D. Bassar; Dylan Z. Childs; Mark Rees; Shripad Tuljapurkar; David N. Reznick; Tim Coulson (Ecology Letters, 2016)
The effects of asymmetric interactions on population dynamics has been widely investigated, but there has been little work aimed at understanding how life history parameters like generation time, life expectancy and the variance in lifetime reproductive success are impacted by different types of competition. We develop a new framework for incorporating trait‐mediated density‐dependence into size‐structured models and use Trinidadian guppies to show how different types of competitive interactions impact life history parameters. Our results show the degree of symmetry in competitive interactions can have dramatic effects on the speed of the life history. For some vital rates, shifting the competitive superiority from small to large individuals resulted in a doubling of the generation time. Such large influences of competitive symmetry on the timescale of demographic processes, and hence evolution, highlights the interwoven nature of ecological and evolutionary processes and the importance of density‐dependence in understanding eco‐evolutionary dynamics.

The effect of soil pH on persistence of seeds of grassland species in soil - Sofía Basto; Ken Thompson; Mark Rees (Plant Ecology, 2015)

Competition on productivity gradients – what do we expect? - Mark Rees (Ecology Letters, 2013)
Many experimental studies have quantified how the effects of competition vary with habitat productivity, with the results often interpreted in terms of the ideas of Grime and Tilman. Unfortunately, these ideas are not relevant to many experiments, and so we develop an appropriate resource competition model and use this to explore the effects of habitat productivity on the intensity of competition. Several mechanisms influencing the productivity–competition intensity relationship are identified, and these mechanisms explored using two classic data sets. In both cases, there is good agreement between the model predictions and empirical patterns. Quantification of the mechanisms identified by the models will allow the development of a simple predictive theory linking measures of the intensity of competition with ecosystem‐level properties.

Identifying the demographic processes relevant for species conservation in human-impacted areas: does the model matter? - Edgar J. González; Mark Rees; Carlos Martorell (Oecologia, 2013)

Influences of Sampling Methodologies on Pesticide-Residue Detection in Stream Water - Zisheng Xing; Lien Chow; Herb Rees; Fanrui Meng; Sheng Li; Bill Ernst; Glenn Benoy; Tianshan Zha; L. Mark Hewitt (Archives of Environmental Contamination and Toxicology, 2013)

Pesticide Application and Detection in Variable Agricultural Intensity Watersheds and Their River Systems in the Maritime Region of Canada - Zisheng Xing; Lien Chow; Art Cook; Glenn Benoy; Herb Rees; Bill Ernst; Fanrui Meng; Sheng Li; Tianshan Zha; Clair Murphy; Suzanne Batchelor; L. Mark Hewitt (Archives of Environmental Contamination and Toxicology, 2012)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Adenosine regulates thrombomodulin and endothelial protein C receptor expression in folliculostellate cells of the pituitary gland - D. Aled Rees; Peter Giles; Mark D. Lewis; Jack Ham (Purinergic Signalling, 2010)

The costs and benefits of fast living - Karen E. Rose; Rebecca L. Atkinson; Lindsay A. Turnbull; Mark Rees (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1379–1384 Abstract Growth rates play a fundamental role in many areas of biology (Q. Rev. Biol., 67, 1992, 283; Life History Invariants. Some Explorations of Symmetry in Evolutionary Biology, 1993; Philos. Trans. R. Soc. Lond. B Biol. Sci., 351, 1996, 1341; Plant Strategies, Vegetation Processes, and Ecosystem Properties, 2002; Trends Ecol. Evol., 18, 2003, 471; Q. Rev. Biol., 78, 2003, 23; J. Ecol., 95, 2007, 926.) but the cost and benefits of different growth rates are notoriously difficult to quantify (Q. Rev. Biol., 72, 1997, 149; Funct. Ecol., 17, 2003, 328). This is because (1) growth rate typically declines with size and yet the most widely used growth measure – relative growth rate or RGR (conventionally measured as the log of the ratio of successive sizes divided by the time interval) – is not size‐corrected and so confounds growth and size, (2) organisms have access to different amounts of resource and (3) it is essential to allow for the long‐term benefits of larger size. Here we experimentally demonstrate delayed costs and benefits of rapid growth in seven plant species using a novel method to calculate size‐corrected RGR. In control treatments, fast‐growing plants benefited from increased reproduction the following year; however, fast‐growing plants subjected to an experimental stress treatment (defoliation) showed strongly reduced survival and reproduction the following year. Importantly, when growth was estimated using the classical RGR measure, no costs or benefits were found. These results support the idea that life‐history trade‐offs have a dominant role in life‐history and ecological theory and that the widespread failure to detect them is partly due to methodological shortcomings.

Why equalising trade‐offs aren’t always neutral - Lindsay A. Turnbull; Mark Rees; Drew W. Purves (Ecology Letters, 2008)
Equalising trade‐offs, such as seed mass vs. number, have been invoked to reconcile neutral theory with observed differences between species. This is an appealing explanation for the dramatic seed size variation seen within guilds of otherwise similar plants: under size‐symmetric competition, where resource capture is proportional to mass, the outcome of competition should be insensitive to whether species produce many small seeds or few large ones. However, under this assumption, stochastic variation in seed rain leads to exclusion of all but the smallest‐seeded species. Thus stochasticity in seed arrivals, a process that was previously thought to generate drift, instead results in deterministic competitive exclusion. A neutral outcome is possible under one special case of a more general equalising framework, where seed mass affects survival but not competition. Further exploration of the feasibility of neutral trade‐offs is needed to understand the respective roles of neutrality and niche structure in community dynamics.

Disturbance, invasion and re‐invasion: managing the weed‐shaped hole in disturbed ecosystems - Yvonne M. Buckley; Benjamin M. Bolker; Mark Rees (Ecology Letters, 2007)
We aim to develop a simple model to explore how disturbance and propagule pressure determine conditions for successful invasion in systems where recruitment occurs only in disturbed sites. Disturbance is often thought to favour invaders as it allows recruitment; however, the effects of disturbance are more complicated when it results in mortality of the invader. When disturbance rates in both invader occupied and unoccupied sites are the same, recruitment and mortality effects are exactly balanced, and successful invasion is independent of the disturbance regime. Differences in the disturbance rates between invader occupied and unoccupied sites can occur through invader modification or management of disturbance. Under these conditions, we found a novel mechanism for the generation of an Allee effect, which occurs when the invader promotes disturbance in sites it already occupies. When Allee effects occur one‐off, large‐scale disturbances can result in permanent, dramatic shifts in invader abundance; and conversely, reducing the population below a critical threshold can cause extinction.

Commentary: Resolving the biodiversity paradox - Peter Chesson; Mark Rees (Ecology Letters, 2007)

Seed bank persistence of clonal weeds in contrasting habitats: implications for control - Elze Hesse; Mark Rees; Heinz Müller-Schärer (Plant Ecology, 2007)

Decoupling the direct and indirect effects of nitrogen deposition on ecosystem function - Pete Manning; John E. Newington; Helen R. Robson; Mark Saunders; Till Eggers; Mark A. Bradford; Richard D. Bardgett; Michael Bonkowski; Richard J. Ellis; Alan C. Gange; Susan J. Grayston; Ellen Kandeler; et al. (Ecology Letters, 2006)
Elevated nitrogen (N) inputs into terrestrial ecosystems are causing major changes to the composition and functioning of ecosystems. Understanding these changes is challenging because there are complex interactions between ‘direct’ effects of N on plant physiology and soil biogeochemistry, and ‘indirect’ effects caused by changes in plant species composition. By planting high N and low N plant community compositions into high and low N deposition model terrestrial ecosystems we experimentally decoupled direct and indirect effects and quantified their contribution to changes in carbon, N and water cycling. Our results show that direct effects on plant growth dominate ecosystem response to N deposition, although long‐term carbon storage is reduced under high N plant‐species composition. These findings suggest that direct effects of N deposition on ecosystem function could be relatively strong in comparison with the indirect effects of plant community change.

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

On the mechanisms of coexistence among annual-plant species, using neighbourhood techniques and simulation models - David A. Coomes; Mark Rees; Lindsay Turnbull; Sophia Ratcliffe (Plant Ecology, 2002)

Interactions between density‐dependent processes, population dynamics and control of an invasive plant species, Tripleurospermum perforatum (scentless chamomile) - Yvonne M. Buckley; Hariet L. Hinz; Diethart Matthies; Mark Rees (Ecology Letters, 2001)
Tripleurospermum perforatum is an invasive weedy species which exhibits strong over‐compensating density dependence. Interactions between density‐dependent survival, probability of flowering and fecundity were modelled and their impact on the population dynamics were examined. When only fecundity was density‐dependent, the dynamics were similar to those observed in the model containing all three density‐dependent terms. Density‐dependent survival was a stabilizing process when acting in combination with density‐dependent fecundity and probability of flowering; removing density‐dependent survival from the model produced two‐point cycles. The addition of a seed bank was also stabilizing. Simulations of control strategies at different life‐history stages indicated that full control would be difficult due to the strong over‐compensating density dependence, with severe reductions in fecundity and late season survival necessary in order to reduce equilibrium seed density and biomass.

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)